2012
DOI: 10.1088/1674-1056/21/7/077102
|View full text |Cite
|
Sign up to set email alerts
|

Structural, elastic, phonon and electronic properties of a MnPd alloy

Abstract: The structural, elastic, phonon and electronic properties of a MnPd alloy have been investigated using the firstprinciples calculation. The calculated lattice constants and electronic structure agree well with the experimental results. The microscopic mechanism of the diffusionless martensitic transition from the paramagnetic B2 (PM-B2) phase to the antiferromagnetic L1 0 (AFM-L1 0) phase through the intermediate paramagnetic L1 0 (PM-L1 0) phase has been explored theoretically. The obtained negative shear mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…11(a)) agrees with the calculation in Ref. [17]. For both ideal and defective structures, the peak at ≈ −2.5 eV is formed by strong Pd-Mn hybridization with equal contributions from Mn and Pd atoms.…”
Section: Dependence Of the Vertical Shift On The Annealing Temperaturesupporting
confidence: 88%
See 2 more Smart Citations
“…11(a)) agrees with the calculation in Ref. [17]. For both ideal and defective structures, the peak at ≈ −2.5 eV is formed by strong Pd-Mn hybridization with equal contributions from Mn and Pd atoms.…”
Section: Dependence Of the Vertical Shift On The Annealing Temperaturesupporting
confidence: 88%
“…The calculated lattice parameters of a = 2.82 Å and c = 3.69 Å agree with the experimental values in this work and Refs. [15,17] and with ab initio calculations [23]. The obtained lattice constants are nearly the same for both ideal L1 0 -PdMn and for the structure with Pd-excess.…”
Section: Modelingmentioning
confidence: 61%
See 1 more Smart Citation
“…where E(V ) is the ground-state total energy at a given unit cell volume V , F vib (T,V ) is the vibrational energy of the lattice ions, and F el (T,V ) is the thermal electronic contribution to the free energy, which can be expressed by electronic entropy S ele (T,V ) and energy due to the electron excitations E ele (T,V ). Under quasi-harmonic approximation (QHA), [17][18][19][20][21] the F vib (T,V ) can be calculated by…”
Section: Theory and Calculation Methodsmentioning
confidence: 99%
“…[7] The addition of Mn to Pd crystal induces a diffusionless martensitic transition and shows significant changes in elastic and phonon properties. [8] Previous studies also revealed that Fe-Pd exhibited a competition between the BCC (Pd-poor and low-temperature) structure and the FCC (Pd-rich and/or high-temperature) structure. [9] Further, the Cu-Pd alloy with Pd concentration greater than 50 at% has a disordered FCC structure, while with Pd less than 18 at% it has an L1 2 -type structure and with 36 at%-46 at% Pd it has an L1 0 -type structure.…”
Section: Introductionmentioning
confidence: 95%